1987
DOI: 10.1016/0168-583x(87)90229-1
|View full text |Cite
|
Sign up to set email alerts
|

Indications of pleistocene man on Sardinia

Abstract: Human fossils found in a Pre-Neolithic cave deposit (Corbeddu cave, Sardinia) represent the first human remains associated with an endemic impoverished island fauna. Radiocarbon dating by AMS in Utrecht provided the chronological framework of the cave sediments for better understanding of the time-related human activities. The aberrant morphology of the human fossils and the unique character of worked deer bones discovered, suggest the development of an endemic Pleistocene human culture, adapted to the restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The ancestry of this cervid has been identified in the Early-Middle Pleistocene continental species Praemegaceros verticornis (Azzaroli, 1961;Caloi and Palombo, 1995 and references therein) which dispersed towards the Corsican -Sardinian paleobioprovince close to the EarlyeMiddle Pleistocene boundary, at a regressive phase of the sea level. Previous studies point to an extinction of P. cazioti around 9000 yBP due to the arrival of Mesolithic humans on the Sardinian island (Sondaar, 2000;Sondaar and Van der Geer, 2002;Vigne et al, 2002), as suggested by the remains found in the Corbeddu Cave (Klein Hofmeijer et al, 1987;Klein Hofmeijer, 1997). Accurate dating of fossils in the Juntu cave would be therefore of noticeable importance in order to better understand this extinction event in the Sardinia region.…”
Section: Introductionmentioning
confidence: 90%
“…The ancestry of this cervid has been identified in the Early-Middle Pleistocene continental species Praemegaceros verticornis (Azzaroli, 1961;Caloi and Palombo, 1995 and references therein) which dispersed towards the Corsican -Sardinian paleobioprovince close to the EarlyeMiddle Pleistocene boundary, at a regressive phase of the sea level. Previous studies point to an extinction of P. cazioti around 9000 yBP due to the arrival of Mesolithic humans on the Sardinian island (Sondaar, 2000;Sondaar and Van der Geer, 2002;Vigne et al, 2002), as suggested by the remains found in the Corbeddu Cave (Klein Hofmeijer et al, 1987;Klein Hofmeijer, 1997). Accurate dating of fossils in the Juntu cave would be therefore of noticeable importance in order to better understand this extinction event in the Sardinia region.…”
Section: Introductionmentioning
confidence: 90%
“…An Upper Palaeolithic human phalanx was indirectly dated by 14 C ages and stratigraphic correlations between two trenches at about 20 ky, while the Epipalaeolithic human remains found in one of these trenches were dated by 14 C at 8750 AE 140 BP. Obsidian was absent in these excavations [33,32,51e53], as in the only two other known Epipalaeolithic sites of Sardinia [20,21,31,32,55,56]. All are coastal or subcoastal sites, probably related to occasional trips or short seasonal settlements on the island.…”
Section: Introductionmentioning
confidence: 97%
“…Τα κροκαλοπαγή είναι οφιολιθικά, με μέγεθος κροκαλών που ποικίλλει από θέση σε θέση. Ακολουθεί η απόθεση κάτω-μειοκαινικών πηλιτών, οι οποίοι εμφανίζουν έντονη τεκτονική καταπόνηση και εναλλάσσονται με ενστρώσεις μικρού πάχους αργίλων, ψαμμιτών, ψαμμιτοκροκαλοπαγών, λεπτόκοκκων άμμων και κροκαλοπαγών Doukas, 1986;Klein Hofmeijer et al, 1987 (Guernet, 1971).…”
Section: αποθέσεις λεκάνης λίμνης-ιστιαίαςunclassified